1987
DOI: 10.1016/s0140-1971(87)80030-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical abuse, sexual victimization and illicit drug use: A structural analysis among high risk adolescents

Abstract: The relationships between child physical and sexual abuse and illicit drug use are relatively unexplored and obscure. Data gathered from a sample of youths in a juvenile detention center permitted an examination of this important issue. A structural model, specifying the influence of child physical and sexual abuse variables on the youths' illicit drug use, directly and as mediated by self‐derogation, was estimated among male and female detainees. Results suggest that for both gender groups, sexual victimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(46 citation statements)
references
References 28 publications
0
42
0
3
Order By: Relevance
“…In the context of typical adolescent experimentation with substance use, adolescents who have been traumatized by abuse may find the effects of substance use to be extremely powerful (e.g., anxiolytic properties of alcohol may be reinforcing for reducing posttraumatic anxiety). Self-dysfunction models have to do with maltreatment-related self-derogation (or low self-esteem) that may result in attempts to escape emotional pain by engaging in substance abuse (e.g., Dembo et al 1987Dembo et al , 1989Feiring et al 1996). Relationship difficulty models focus on the possible effects of early and adolescent relationships with parents on social development and thus, later relationships, with parents, peers, and partners (Brook et al 2006;Brook et al 2009;Crittenden and Claussen 2002).…”
Section: Explanatory Models Of the Link Between Child Maltreatment Anmentioning
confidence: 99%
“…In the context of typical adolescent experimentation with substance use, adolescents who have been traumatized by abuse may find the effects of substance use to be extremely powerful (e.g., anxiolytic properties of alcohol may be reinforcing for reducing posttraumatic anxiety). Self-dysfunction models have to do with maltreatment-related self-derogation (or low self-esteem) that may result in attempts to escape emotional pain by engaging in substance abuse (e.g., Dembo et al 1987Dembo et al , 1989Feiring et al 1996). Relationship difficulty models focus on the possible effects of early and adolescent relationships with parents on social development and thus, later relationships, with parents, peers, and partners (Brook et al 2006;Brook et al 2009;Crittenden and Claussen 2002).…”
Section: Explanatory Models Of the Link Between Child Maltreatment Anmentioning
confidence: 99%
“…Dembo and colleagues have conducted a series of studies examining the mediating role of self-derogation (i.e., low global self-esteem) between physical and sexual victimization in childhood and later substance use (Dembo et al, 1987;Dembo et al, 1989). Using data from detainees in a juvenile detention center, they found that self-derogation partially mediated the effects of physical and sexual abuse on substance use; both types of abuse continued to have direct effects on substance use as well.…”
Section: Depressive Self-conceptmentioning
confidence: 99%
“…These kinds of behavior certainly are ab-errant and deviant when set against the adult standard of acceptable behavior, but with half or more adolescents reporting that they have experienced drunk driving (Arnett, 1990a), sex without contraception (Zelnik & Kantner, 1980), illegal drug use (U.S. Department of Education, 1988), and some form of minor criminal activity (Farrington, 1989), reckless behavior becomes virtually a normative characteristic of adolescent development. It is true that reckless behavior may be in some cases a reflection of psychopathology (Brill & Cristie, 1974) or of pathogenic family conditions (Dembo, Dertke, laVoie, & Bonders, 1987), or at least partly a response to parental neglect, hostility, or absence (Davis & Cross, 1973;Hansson, O'Conner, Jones, & Blocker, 1981;Johnson, Shontz, & Locke, 1984;Stern, Northmn, & Van Slyck, 1984). But the very prevalence of reckless behavior calls into question the common assumption that it necessarily arises from pathological personal characteristics or from pathogenic socialization practices or that reckless behavior is always deviant behavior for adolescents.…”
Section: Multiple Reckless Behaviormentioning
confidence: 99%